(untitled) (Nigerian Journal of Technology, 2024)
3D-printed carbon fibre-reinforced composites (CFRC) using fused deposition modelling (FDM) offer the potential for building complex geometries and low waste. However, these composites have weaker interlaminar bonding and higher void content than traditional composites. This paper explores the effect of temperature on improving the mechanical properties of 3D-printed short carbon fibre-reinforced polyamide (PACF). Two types of printed structures were tested: one with a 0° build orientation (parallel to extruder movement) and the other with a 90° build orientation (perpendicular to extruder movement). Both samples were heat-treated at 150°C. Force vs. displacement data was obtained from the MTS testing machine. After that, the tested samples were viewed under an optical microscope. Images obtained from the optical microscope are then analyzed to see how the samples failed by checking the microstructure. The average ultimate strength, ultimate strain, and elastic modulus were used for the analysis. The sample follows a trend where the strength and elastic modulus increase after heat treatment. The result also showed that the 0° build orientation samples have higher mechanical performance than the 90° build orientation sample. Also, from the ultimate strain values, it was evident that samples printed in the 0° absorbed more energy, exhibiting 83% higher resistance before final failure. Lastly, an optical microscope was used to investigate the failure mechanisms of the samples.